MITIGASI BENCANA KEBAKARAN LAHAN GAMBUT DENGAN MENGGUNAKAN METODE ALAT PENGGALI AIR INSITU DAN PERAN SERTA MASYARAKAT DI DESA RIMBO PANJANG, KABUPATEN KAMPAR, PROVINSI RIAU - Ary Junaidy, Ari Sandhyavitri, Muhamad Yusa (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2019)
Reducing the risk of forest fires needs to be assessed and improved the patterns and practices of forest resource management and the people who live around the forest. This must be formulated in a coping strategy so that the risk of forest fires is reduced. This research aims to explore information on efforts to prevent and combat land fires that have been carried out by the community and the Fire Concern Community group in Rimbo Panjang Village, Kampar Regency, Riau Province; Knowing the potential availability of groundwater on peatlands at the location of land fires; and Assessing the peatland fire extinguisher system by making fire extinguisher wells quickly, precisely and accurately at the location of the fire. The method used in this research is qualitative and quantitative. Qualitative data based on questionnaire analysis from relevant stakeholders. While the quantitative one is calculating the availability of water in the location of peatland fires. Based on the analysis, it was found that the efforts to prevent and overcome land fires that have been carried out by the community and the Fire Concern Community group before the fire occurred are to create water reservoirs (canal blocking, storage ponds, etc.); (ii) the time of fire is finding water for fire fighting and (iii) after the fire is Fire Law Enforcement. The potential availability of groundwater obtained at 1066,167 m3 / day can be used to extinguish fires in peatlands. Efforts are made to get this water is by making fire extinguishing wells quickly, precisely and accurately at the location of the fire using a mobile water digger.